2012
DOI: 10.1590/s0103-84782012005000005
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade química, físico-química e microbiológica de polpas de acerola pasteurizadas e não-pasteurizadas de cultivo orgânico

Abstract: IIEstabilidade química, físico-química e microbiológica de polpas de acerola pasteurizadas e não-pasteurizadas de cultivo orgânico Chemical, physicochemical and microbiological stability of pasteurized and non pasteurized acerola pulps from organic cultivation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 8 publications
5
7
0
9
Order By: Relevance
“…Changes of this nature are, probably, commercially irrelevant, considering that the pulp will be diluted to prepare juices or used as an ingredient in different culinary preparations. The downward trend observed for pH is similar to that reported in a study evaluating the effects of freezing, pasteurization, and storage for 360 days on acerola pulp (Lima et al, ),…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Changes of this nature are, probably, commercially irrelevant, considering that the pulp will be diluted to prepare juices or used as an ingredient in different culinary preparations. The downward trend observed for pH is similar to that reported in a study evaluating the effects of freezing, pasteurization, and storage for 360 days on acerola pulp (Lima et al, ),…”
Section: Resultssupporting
confidence: 87%
“…Nevertheless, the effect of these alterations on the visual appeal of the product can only be explained by sensory analysis. Corroborating these results, Lima et al () found a decrease in C * of pasteurized and unpasteurized acerola pulp during frozen storage (−18 ± 2°C) for 360 days. Studies on the stability of fruit pulps have reported changes in the color induced by pasteurization, freezing methods, temperature, and storage time (Aquino, Carnelossi, & Castro, ; Damiani et al, ; Lima et al, ), as identified in this present study.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Moura et al (2007) -1 e 0,99 g.100 g -1 de ácido málico. Lima et al (2012) consideram esse parâmetro importante do ponto de vista tecnológico, pois está diretamente relacionado à sua qualidade quanto ao atributo sabor, sendo mais atrativo para o consumo in natura.…”
Section: Resultsunclassified
“…Em todo o mundo se observa um aumento expressivo no consumo de frutas tropicais por suas propriedades e funcionalidades [1]. No Brasil, a cultura da acerola (Malpighia emarginata) oferece grandes possibilidades de sucesso, devido às ações climáticas favoráveis, principalmente na parte tropical do território nacional e pelo aspecto nutricional para a saúde pública, particularmente das populações economicamente mais carentes [2].…”
Section: Introductionunclassified